2020
DOI: 10.1021/acs.est.0c02963
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of High-Resolution Atmospheric Mercury Emission Inventories for Chinese Cement Plants Based on the Mass Balance Method

Abstract: China is the world's largest cement-related mercury emitter. Atmospheric mercury inventories for China's cement industry are essential for appraising global mercury emissions and have been widely developed in previous studies associated with considerable uncertainties. In this study, we compiled high tempospatial resolution atmospheric mercury emission inventories for Chinese cement plants using the mass balance method and plantlevel input−output data. The effects of industry policies were investigated based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Monte Carlo simulation was employed to generate the probabilistic distribution of atmospheric NH 3 emissions in each industrial sector, , and we ran the models for 10 000 iterations in accordance with previous studies. The distribution of industrial NH 3 concentrations was set following published literature .…”
Section: Methodsmentioning
confidence: 99%
“…Monte Carlo simulation was employed to generate the probabilistic distribution of atmospheric NH 3 emissions in each industrial sector, , and we ran the models for 10 000 iterations in accordance with previous studies. The distribution of industrial NH 3 concentrations was set following published literature .…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, the impact of anthropogenic emissions changes was often quantified by compiling emission inventories (Zhang et al, 2015;Wu et al, 2016;K. Liu et al, 2019;Cai et al, 2020). The trajectory-based analysis method was frequently applied to analyze the impact of regional transport (Tang et al, 2018;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, based on data of the continuous emission monitoring system (CEMS), Tang et al estimated emissions of PM, SO 2 , and NOx in 2018 were 0.07, 0.09, and 0.88 Mt, respectively. In addition, some studies conducted relevant estimations on mercury emissions, , and Hua et al were also concerned about emissions of some other toxic trace elements (e.g. Cd, Cr, Pb, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al indicated that clinker production was the largest source of anthropogenic atmospheric Hg emissions in China after 2009, with emissions of 145 t in 2014 (27.4% of national emissions). Based on mass balance method with plant-level data, Cai et al estimated that the atmospheric Hg emissions of the national cement industry increased from 80 t (2007) to 113 t (2015). As for CO 2 emissions, more and more studies had gradually focused on updating localized emission factors (EFs) to better reflect the real world of Chinese cement production. ,, Shen et al calculated the CO 2 EFs by analyzing samples from 359 cement production lines nationwide, finding that the values suggested by international institutes were slightly overestimated, and fuel-related CO 2 EFs were mainly underestimated. , Thus, it is necessary to update and summarize EFs with unit-level activity data for the new estimates of air pollutants and CO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%